2022
DOI: 10.3390/jrfm15060272
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Certificate-of-Need Laws on the Quality of Hospital Medical Services

Abstract: Certificate-of-need (CON) laws restrict entry into health services by requiring healthcare providers to seek approval from state healthcare regulators before making any major capital expenditures. An important question is whether CON laws influence the quality of medical services in CON law states. For instance, if CON laws actually lower the quality of medical services, they fail to achieve their intended effect. This paper tests the hypothesis that hospitals in states with CON laws provide lower-quality serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Similarly, papers by Stratmann and Wille (2016) and Stratmann (2022) found that mortality and readmission rates were higher in regulated states, concluding that CON led to lower quality care for some measures of quality. CON may also be associated with lower quality care in the nursing home industry (Fayissa et al, 2020).…”
Section: A Previous Research On the Effects Of Certificate Of Need Re...mentioning
confidence: 94%
“…Similarly, papers by Stratmann and Wille (2016) and Stratmann (2022) found that mortality and readmission rates were higher in regulated states, concluding that CON led to lower quality care for some measures of quality. CON may also be associated with lower quality care in the nursing home industry (Fayissa et al, 2020).…”
Section: A Previous Research On the Effects Of Certificate Of Need Re...mentioning
confidence: 94%
“…1,2 These regulations vary in scope by state and aim to control health care costs, avoid unnecessary duplication of services in an area, and ensure access to services for underserved or rural communities. 1,3,4 When these laws are in place, approval is needed by state planning agencies before expanding certain health care services and approving capital expenditures. 2 Due in part to federal incentives, CON statutes peaked in the United States in 1980 in 49 states, but by later that decade, when federal support was withdrawn, 12 states began to repeal their CON laws.…”
Section: Introductionmentioning
confidence: 99%